Palm-O-Lite promotes healthy lifestyle, resolves cooking oil issues - Nor Salwana, Mohammad Idris (2019)
Concerned about the negative habit of Malaysians who love to use more-than-necessary oil when cooking – which tend to result in accumulation of saturated fat in their bodies – three researchers at Universiti Malaysia Pahang (UMP) have collaborated to produce Palm-O-Lite, a palm-oil based aerosol to be used in culinary industry to facilitate cooking while simultaneously promoting a healthy lifestyle.